Decentralization of Health Financing Policies Legal Implications for Equitable Distribution of Health Services - Ajeng Herfiana; Liony Fryonita Kolintama (Bacarita Law Journal, 2026)
The decentralization of health financing policy in Indonesia has generated complex legal dynamics in efforts to equalize health services across regions. This study analyzes the legal implications of fiscal health authority delegation under Law Nomor 23 of 2014 on Local Government and its derivatives on the accessibility and quality of primary and secondary health services at the local level. Employing a normative juridical approach with qualitative analysis of policy documents, regional fiscal data, and administrative court decisions, the research reveals financing disparities due to uneven regional fiscal capacity and weak central oversight. Findings indicate that decentralization tends to undermine equity owing to budget fragmentation and inconsistent legal implementation, despite potential for enhanced local responsiveness to epidemiological needs. Reforms are recommended through strengthened performance-based fiscal transfers and cross-level accountability mechanisms to realize constitutional health justice as mandated by Article 34 of the 1945 Constitution.